Image Segmentation to Secure LSB2 Data Steganography - Zaini, H. G. (Engineering, Technology & Applied Science Research, 2021)
A digital color image usually has a high resolution, thus its size is good enough and the image can be used as a covering (holding) image to hide secrete messages (short and long). The methods commonly used for data steganography, e.g. LSB and LSB2 are not secure, so in this paper, a method of securing the LSB2 method is proposed. The proposed method is based on wavelet packet decomposition. The levels of decomposition will be kept in secret and one of the resulting segments will be used as a covering segment. MSE, PSNR, hiding time, and extraction time will be experimentally analyzed to prove that the proposed method is capable of handling the process of hiding secret messages, either sort or long.